The Relationship of Hedonic Hunger With Depression and Physical Activity in Students of Faculty of Health Sciences - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2022)
The study was conducted to examine the hedonic hunger, physical activity, and depression status of healthy university students and to reveal the relationship between these parameters. A total of 174 healthy university students were included in the study. Hedonic hunger responses were similar at different physical activity levels. When the relationship between individuals' hedonic hunger responses and intensity of depression was examined, it was found that there was a weak positive correlation between them. Hedonic hunger can have negative effects on university students' depression status. Taking precautions to improve nutrition and physical activity in university students can be effective in preventing this problem.
Keywords: depression; hedonic hunger; physical activity; university students; ACTIVITY QUESTIONNAIRE; DIETARY PATTERNS; EXERCISE; ADULT; RELIABILITY; ASSOCIATION; ADOLESCENT; QUALITY; RISK